(untitled) (Comparative Professional Pedagogy, 2023)
The collection of scientific papers highlights the results of the research into certain aspects of the Polish labor market functioning during the global COVID-19 pandemic. It became a challenge for the whole world and significantly affected all spheres of social life, including the labor market. The new reality faced by the labor market requires effective and well-thought-out actions that would allow to perform professional tasks and duties, carry out new searches, and significantly change the established work routine. Now a new post-pandemic reality has emerged. With the relaxation of restrictions, the realities of life have changed and they will never be the same as before the pandemic. The stable production environment has also changed, and the level of employees’ and employers’ welfare has decreased. Everyone has to overcome new difficulties.